Research on Slope Stability Evaluation Based on Improved Set Pair Analysis Method: A Case of Tonglvshan Open-Pit Mine - Xiaojie Yang; Zhenli Hao; Gaotong Ma; Gan Li (Shock and Vibration)
In this paper, combined with fuzzy analytic hierarchy process (FAHP), information entropy theory, and set pair analysis (SPA) theory, an improved set pair analysis model (EFAHP-SPA) for open-pit mine slope stability evaluation based on entropy method and FAHP is proposed. Taking the east-side slope of Tonglvshan north open-pit mine in Daye as an example, the proposed method is verified. First, an open-pit mine slope stability evaluation index system with 14 indicators in 4 categories, namely the topography and geomorphology, geological structure, hydrogeology, and other factors, have been constructed. Second, the objective weight and subjective weight of each evaluation index are calculated by entropy and fuzzy analytic hierarchy process, and then the comprehensive weight of the evaluation index is estimated based on subjective weight and objective weight. Afterward, the single-index connection degree between the evaluation index and the evaluation standard of the secondary subsystem is evaluated considering the improved set pair analysis theory, and the comprehensive connection degree of the system is obtained by combining it with the comprehensive weight of each evaluation index. Finally, the confidence criterion is established to discern the risk grade of slope stability in the east-side slope of the north open pit in Daye Tonglvshan mine. Moreover, case studies and comparisons of the proposed model with fuzzy comprehensive evaluation method and Entropy-SPA model were performed to confirm the validity and reliability. The results show that the evaluation results of the proposed EFAHP-SPA model are consistent with the actual situation of open-pit mines and the evaluation results of entropy-SPA model and are somewhat different from those of fuzzy comprehensive evaluation method. It indicates that the proposed EFAHP-SPA evaluation model can objectively evaluate the slope stability of the open-pit mine.